Solving the preoperative breast MRI conundrum: design and protocol of the MIPA study - Sardanelli, Francesco; Trimboli, Rubina M.; Houssami, Nehmat; Gilbert, Fiona J.; Helbich, Thomas H.; Alvarez Benito, Marina; Balleyguier, Corinne; Bazzocchi, Massimo; Bult, Peter; Calabrese, Massimo; Camps Herrero, Julia; Cartia, Francesco; et al. (European Radiology, 2020)
Despite its high diagnostic performance, the use of breast MRI in the preoperative setting is controversial. It has the potential for personalized surgical management in breast cancer patients, but two of three randomized controlled trials did not show results in favor of its introduction for assessing the disease extent before surgery. Meta-analyses showed a higher mastectomy rate in women undergoing preoperative MRI compared to those who do not. Nevertheless, preoperative breast MRI is increasingly used and a survey from the American Society of Breast Surgeons showed that 41% of respondents ask for it in daily practice. In this context, a large-scale observational multicenter international prospective analysis (MIPA study) was proposed under the guidance of the European Network for the Assessment of Imaging in Medicine (EuroAIM). The aims were (1) to prospectively and systematically collect data on consecutive women with a newly diagnosed breast cancer, not candidates for neoadjuvant therapy, who are offered or not offered breast MRI before surgery according to local practice; (2) to compare these two groups in terms of surgical and clinical endpoints, adjusting for covariates. The underlying hypotheses are that MRI does not cause additional mastectomies compared to conventional imaging, while reducing the reoperation rate in all or in subgroups of patients. Ninety-six centers applied to a web-based call; 36 were initially selected based on volume and quality standards; 27 were active for enrollment. On November 2018, the target of 7000 enrolled patients was reached. The MIPA study is presently at the analytic phase. Key Points center dot Breast MRI has a high diagnostic performance but its utility in the preoperative setting is controversial. center dot A large-scale observational multicenter prospective study was launched to compare women receiving with those not receiving preoperative MRI. center dot Twenty-seven centers enrolled more than 7000 patients. The study is presently at the analytic phase.
CRIS-Team WoS Importer:2020-05-15